2018
DOI: 10.1142/s201032631840004x
|View full text |Cite
|
Sign up to set email alerts
|

On the quasi-Ablowitz–Segur and quasi-Hastings–McLeod solutions of the inhomogeneous Painlevé II equation

Abstract: We consider the quasi-Ablowitz-Segur and quasi-Hastings-McLeod solutions of the inhomogeneous Painlevé II equationThese solutions are obtained from the classical Ablowitz-Segur and Hastings-McLeod solutions via the Bäcklund transformation, and satisfy the same asymptotic behaviors when x → ±∞. For |α| > 1/2, we show that the quasi-Ablowitz-Segur and quasi-Hastings-McLeod solutions possess [ |α| + 1 2 ] simple poles on the real axis, which rigorously justifies the numerical results in Fornberg and Weideman (Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, the numerical computations performed in [19] suggested that the qAS solution determined by the parameters (1.14) has exactly n poles on the real line. Recently, the predictions were rigorously justified in [14], where results concerning the residues of these poles were also obtained. If we put α = 0 and allow the parameter k to be an arbitrary complex number, then we call u(x; 0, k) the complex AS solution for the homogeneous PII equation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the numerical computations performed in [19] suggested that the qAS solution determined by the parameters (1.14) has exactly n poles on the real line. Recently, the predictions were rigorously justified in [14], where results concerning the residues of these poles were also obtained. If we put α = 0 and allow the parameter k to be an arbitrary complex number, then we call u(x; 0, k) the complex AS solution for the homogeneous PII equation.…”
Section: Introductionmentioning
confidence: 99%
“…2]. If one extends the value of α to |α| > 1 2 and keeps |k| < | cos(πα)|, we have proved that the asymptotic behavior of u(x; α) is the same as the AS solutions, but [ |α| + 1 2 ] simple poles will appear on the real axis; see [16,Thm. 1].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 74%
“…In recent years, the existence and monotonic properties of these HM solutions have been studied in [11,13,36]. See also [16] for the properties of the qHM solutions.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…(iii) For P II with α = 0, there are analogs of the Ablowitz-Segur and Hastings-McLeod solutions, known as the quasi-Ablowitz-Segur solution and the quasi-Hastings-McLeod solution [43,59,60]; see also [49,70,72,134]. There is an extensive literature regarding the asymptotics for P II (1.2) when α = 0.…”
Section: Notation For Painlevé Transcendentsmentioning
confidence: 99%
“…see Dai and Hu [59,60]. For the quasi-Hastings-McLeod solution, Claeys, Kuijlaars and Vanlessen [43] show that there exists a unique solution which is pole-free on the real axis with the asymptotic behaviours…”
Section: Notation For Painlevé Transcendentsmentioning
confidence: 99%